Depressive and anxiety symptoms among university students during the later stages of the COVID-19 pandemic in Germany - Results from the COVID 19 German Student Well-being Study (C19 GSWS) - Heumann, Eileen; Helmer, Stefanie M.; Busse, Heide; Negash, Sarah; Horn, Johannes; Pischke, Claudia R.; Niephaus, Yasemin; Stock, Christiane (Frontiers in Public Health, 2024)
Introduction: Data on the mental health of university students in Germany during the later stages of the pandemic is still limited. This study aimed to determine (1) the prevalence of anxiety and depressive symptoms among university students 1.5 years after the first COVID-19 restrictions and (2) which factors were associated with these outcomes.The cross-sectional COVID-19 German Student Well-being Study (C19 GSWS) collected data of 6,996 students at five German universities. Associations between anxiety and depressive symptoms with sociodemographic and other factors were analyzed using multivariable logistic regression models.The mean age of the participants was 23.9 years (SD= 4.8), 67% were female and 31% male. The prevalence for depressive symptoms was 29% and 32% for anxiety. The lack of a trusted person and financial difficulties were associated with anxiety and depressive symptoms. Being worried that someone in one's personal network had become severely ill with COVID-19 and concern about (re)infection with COVID-19 were associated with anxiety symptoms. Those with pre-existing health conditions had an up to 1.98-times higher chance for reporting depressive symptoms (OR, 95% CI: 1.01-3.88) and an up to 2.27-times higher chance for anxiety symptoms, respectively (OR, 95% CI: 1.15-4.46).Concepts for prevention and counselling to tackle mental health problems in students are needed and programs should take specific stressors in times of crises into account.